Influência da dopagem de Fe/Co sobre as propriedades dielétricas no sistema Bi3.25Nd0.75Ti3O12 - Lozano, Rafael (2025)
With the trends in environmental protection, there is a growing interest and demand in the development of lead-free ferroelectric materials to replace lead-based materials with properties suitable for various technological applications. In this context, bismuth titanate (Bi4Ti3012 - BiT) is a material with a structure of the Aurivillius family, or bismuth layers, with high potential for applications in devices and other technological apparatuses because it presents ferroic and also multiferroic properties due to its compositional manipulation and that mimic some characteristics presented by the dominant material in these applications, lead zirconate titanate (PbZr1−xTixO3 - PZT). In this case, it is possible to tune both the dielectric and ferroelectric properties and add multiferroic and/or photovoltaic properties to the BiT system through doping with chemical elements of interest. In this work, the material Bi3.25Nd0.75Ti(3−x)(Co1/2,Fe1/2)xO12 was prepared using the conventional sintering technique, which is a bismuth titanate modified with neodymium (Nd) in the Bi A site and with iron (Fe) and cobalt (Co) ions in the Ti B site. The effects of the Nd dopant confer to the BIT system the improvement of the electrical polarization, while the co-doping with Fe/Co is motivated by the search for control of the crystal structure and properties, mainly inducing multiferroic properties. Furthermore, the presence of Fe and Co in the bismuth titanate matrix can result in unexplored phenomena, such as additional phase transitions and improvement of the magnetic behavior induced by modifications. Thus, this work proposes to explore the effects of co-doping of cobalt and iron on the dielectric, pyroelectric and ferroelectric properties of the system Bi3.25Nd0.75Ti(3−x)(Co1/2,Fe1/2)xO12, with 0 ≤ x ≤ 0.4 (abbreviated as BNdTFC-x). For this purpose, impedance spectroscopy techniques and pyroelectric properties were explored in samples with different Fe/Co doping compositions, subjected to temperatures between 15 K and 980 K. The analysis allowed to identify ferroelectric-paraelectric phase transitions, as well as to investigate the influence of co-doping on the electrical and dielectric properties of the material. The results demonstrated that the introduction of Fe and Co shifts the transition temperature to higher values, but also influences the electrical conduction mechanisms, impacting the dielectric loss under certain conditions. Furthermore, the variation of critical temperatures with doping suggests relevant structural and electronic modifications, contributing to a better understanding of the ferroelectric behavior of the system. These observations make the material an interesting candidate for applications in electronic devices operating at high temperatures.